Effect of gluten-free diet on autoimmune thyroiditis progression in patients with no symptoms or histology of celiac disease: a meta-analysis - Piticchio, Tommaso; Frasca, Francesco; Malandrino, Pasqualino; Trimboli, Pierpaolo; Carrubba, Nunzia; Tumminia, Andrea; Vinciguerra, Federica; Frittitta, Lucia (Frontiers in Endocrinology, 2023)
Background: Hashimoto's thyroiditis (HT) is the most common autoimmune disease. HT may be associated with nonthyroidal autoimmune diseases, including celiac disease (CD) or other gluten related conditions (GRC). In the last years, interest about gluten free diet (GFD) has increased for its supposed extraintestinal anti-inflammatory effect, so many patients with HT initiate GFD on their own. Objectives: Aim of this meta-analysis is to examine all available data in literature about the effect of a GFD on TgAb, TPOAb, TSH, FT4, and FT3 levels in patients with HT and no symptoms or histology of CD. Methods: The study was conducted according to MOOSE. The search was performed on databases PubMed and Scopus. The last search was performed on February 7, 2023. Quality assessment was performed. Meta-analyses were performed using random-effect model. Hedges'g was used to measure the effect size (ES). Statistical analyses were performed using StataSE 17. Results: The online search retrieved 409 articles and 4 studies with total 87 patients were finally included for quantitative analysis. The risk of bias was generally low. The mean period of GFD was almost 6 months. The meta-analyses showed reduction in antibody levels with ES: -0.39 for TgAb